Pelatihan Pemanfaatan Web Bagi Pemuda Muhammadiyah Cabang Kartasura - Fatmawati, Azizah (WARTA, 2010)
Web is one medium that can be used by many activists in community organizations to actualize themselves and communicate effectively. Web Utilization Training for Muhammadiyah Youth in Kartasura branch is expected to provide knowledge into the importance of mastering Information Technology and increase the understanding of the web (Web Logs) as the more effective information tool (Amar Maâruf Nahi Munkar). The result shows that the implementation of the training is quite successful. This can be seen from the enthusiasm of the participants in providing feedback from the questionnaires delivered before and after the training. Furthermore, the training also shows an increasing knowledge in the use of the web as much as 64%.